The Consumer Journey from Purchase Decision to Word of Mouth at Esperto Cafe - Revalino Tigor Hasudungan; Rusman Efendi Sihombing; Wulandari Asri; Masrina Gultom (MAMEN: Jurnal Manajemen, 2026)
This study examines the influence of product quality on word of mouth (WOM) through the mediating roles of purchase decision and customer satisfaction at Esperto Cafe, Jakarta. Drawing on Watson’s Stimulus-Response (S-R) Theory and the Customer Satisfaction Model, this study employs a quantitative approach. Data were collected in December 2025 from 150 customers selected through purposive sampling and analyzed using SmartPLS 3. The findings indicate that product quality has a positive and significant effect on purchase decision, customer satisfaction, and WOM. Product quality also indirectly influences WOM through purchase decision, which emerges as the strongest mediating mechanism. However, customer satisfaction does not significantly affect WOM and fails to mediate the relationship between product quality and WOM. These findings suggest that, in the context of Jakarta’s urban specialty cafes, consumers’ recommendation behavior is driven more by actual purchasing experiences and repeated transactional behavior than by post-consumption satisfaction alone. The study contributes to the consumer behavior literature by extending Watson’s S-R Theory through a dual-mediation framework that simultaneously compares purchase decision and customer satisfaction as alternative pathways linking product quality to WOM. Managerially, the findings highlight the importance of maintaining consistent product quality and strengthening factors that encourage purchase decisions to stimulate positive consumer recommendations.